Africa and the International Criminal Court. Issue 10 (25th November 2016) - Unknown
Abstract : Although three African countries have recently announced their withdrawals from the International Criminal Court (ICC), a mass exodus does not appear imminent. Perceptions of the Court's bias towards African member-states are exaggerated, and it has begun to challenge major powers. Exceptions to the ICC's prosecutorial obligations allowing member-states greater flexibility to accommodate conflict resolution efforts among other situations could make African member-states less hostile to the Court.